The Effectiveness of Flipped Classroom to Improve Students' Concept Understanding and Self Efficacy during the Covid-19 Pandemic - Marina, Heni; Ridlo, Saiful (FMIPA UNNES, 2021)
The purpose of this study is to analyze the effectiveness of flipped classrooms during the covid-19 pandemic to improve understanding of students' concepts and self efficacy, especially in circulatory system materials. This type of research is a quaration of experiments using non-equivalent control group design. The population is all students of grade XI Mipa SMA N 4 Pekalongan school year 2020/2021. Sampling in this study used purposive sampling technique with selected class XI Mipa 3 and 4. In experimental classes they implement flipped classroom learning while control classes implement non-flipped classroom learning using video conference and assignment methods. Data collection there are two techniques namely test and non-test. The results showed that understanding of student concepts increased after the application of flipped classroom in learning. From 13% of students understand the concept to 55% of students understand the concept. Results N of moderate category experiment class gain 51.43% and high 45.71% while medium category control class 29.40% and high 35.30%. Classical completedness of experimental class learning by 85%. Mann Whitney's test results showed Asymp's value. Sig. (2-tailed) 0.038 < 0.05 so it known that there is a significant difference between the average posttest results of the experimental class and the control class. Self efficacy of students before treatment category is quite high to high by 42.86%. After the treatment of flipped classrooms became 71.43%. The results of the paired sample t-test showed the Asymp value. Sig. (2-tailed) 0.000 <0.05, so it known that there is a significant difference after treatment. Based on these results, it can be concluded that flipped classroom is effective to improve student’s understanding of concepts and self efficacy in circulatory system materials.